Go2Altitude - Health and fitness equipment for intermittent hypoxic training (IHT)
This web site has been constructed to allow you to understand the fundamental differences between intermittent hypoxic training and the other hypoxic stimulation methods. You will see for yourself how GO2AltitudeTM`s IHT regime will benefit you more than other methods of altitude simulation. GO2AltitudeTM is better because we have realised that the best results come from higher altitudes but for shorter periods. The work your body has to do to adjust to multiple changes in altitude over an hour is more beneficial than the work your body has to do to survive in a low oxygen environment overnight. History Hypoxic stimulation has been being used to cure disease and to effect high performance physiological changes in athletes for decades in the former USSR. Since the Olympics in Mexico City in 1968, there has been a marked increase in the interest and application of this method of maximising athletic potential. It has also proven to be highly effective in the treatment of disease and improvement of health and well being. IHT has been demonstrated as a superior approach both in terms of ease of application and benefits acquired.